2011
DOI: 10.3171/2011.9.focus11203
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of an infantile hemangioma in a dorsal root ganglion

Abstract: Infantile hemangiomas are tumors commonly seen in children. Few authors have reported infantile hemangiomas affecting the CNS, and there are no prior reports detailing spontaneous resolution of a histologically proven juvenile hemangioma within a dorsal root ganglion. The authors report the case of a newborn boy with a large cutaneous hemangioma in the midline of his back. Spinal MR images were obtained to rule out associated spinal cord tethering, and an intradural spinal lesion was unexpectedly disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Orbital IH may be associated with intra-CNS component, as reported in the literature and observed in patients 5 and 7 ( 8 ). Thirteen cases of cutaneous IHs with intra-spinal involvement have been reported in the literature ( 6 , 9 , 11 , 13 , 17 ). Interestingly, 3 patients ( 6 , 9 ) presented cutaneous IH on the face, while the intra-spinal localization was at the cervical and dorsal level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orbital IH may be associated with intra-CNS component, as reported in the literature and observed in patients 5 and 7 ( 8 ). Thirteen cases of cutaneous IHs with intra-spinal involvement have been reported in the literature ( 6 , 9 , 11 , 13 , 17 ). Interestingly, 3 patients ( 6 , 9 ) presented cutaneous IH on the face, while the intra-spinal localization was at the cervical and dorsal level.…”
Section: Discussionmentioning
confidence: 99%
“…A few other cases of CNS IH described in the literature have been treated with corticosteroids, interferon, thalidomide, embolization or surgery ( 9 10 , 12 – 16 ). Spontaneous involution has been also reported ( 9 , 17 ).…”
mentioning
confidence: 94%
“…In addition, various infant cases of infantile hemangioma in the spinal canal accompanied by cutaneous infantile hemangioma have been reported. [11][12][13][14][15] Meanwhile, there has been only 1 reported case of infantile hemangioma of the spinal cord without cutaneous infantile hemangioma, that of a 3-year-old girl reported by Steinberger et al 16…”
Section: Rarity Of Infantile Hemangioma In and Around The Spinal Cordmentioning
confidence: 99%
“…There is then a proliferative phase that increases until approximately 18 months of age, followed by regression by about 5 years of age, and disappearance after that, depending on the individual. [20][21][22] Hervey-Jumper et al 12 reported an infantile hemangioma in the L5 dorsal root ganglion that was biopsied, although the lesion regressed after 16 months. Regarding the regression of infantile hemangioma, GLUT-1-positive endothelial cells in infantile hemangioma are facultative stem cells that can take on a stem cell or progenitor cell phenotype under certain conditions.…”
Section: Clinical Characteristics and Treatment Of Infantile Hemangiomamentioning
confidence: 99%